Russia - Kazakov, V. (Comparative elite sport development. Systems, structures and public policy, 2025)
2022 was a pivotal year for Russia. The invasion of Ukraine represented a culmination of external and internal political trends, but nevertheless came as a complete surprise that initiated seismic shifts in Russian political, social, and economic life. Sport, which is a prominent part of both the Kremlin's strategic policies and the public life of Russians, has not escaped this new stark geopolitical reality. Developments in 2022 have already profoundly affected and will continue to have a lasting impact on elite and mass sport in Russia. Two 2022 stories concerning elite Russian sports are indicative of these tidal waves of change: one at the macro-level, and the other on the individual one. As this chapter will show, these stories represent both a continuation of, and departure from, some of the key dynamics that have shaped the Russian sports world in recent decades. This chapter will also illustrate some of the key developments in Russian sports since the publication of previous works in this area (notably, Smolianov, 2013; and, most recently, Arnold, 2021).